Peran PAK Dalam Mengatasi Kesulitan Belajar - Rotua Setiani Sinaga; Rosmelina Naibaho; Maria Widiastuti; Sriwati Sihombing; Tivo Juan Simanjuntak; Yosafat Timothy Limbong (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2022)
The purpose of this research is that those who are studying have a definite goal of gaining as much knowledge as possible and getting good results on exams, for those who are working, the goal is to work as best as possible to complete existing responsibilities and get good income from what they do. . The research method used is a qualitative method in the form of a literature study where the author presents and discusses overcoming PAK Learning Difficulties, and invites all of us to dedicate what we do in our daily lives just to glorify His name. The Lord God will see whether what we are doing glorifies His name or not. By teaching PAK so that more and more souls are saved.